LINGUOSEMIOTIC CLASSIFICATION OF SYMBOLS (World Bulletin of Management and Law, 2025)
Linvosemiotic classification of symbols in Uzbek poetry is analyzed in the article, their lexical meaning and semantic features are highlighted.